The Diverse Structures of Passenger Car Taxation in Europe and the EU Commissions Proposal for Reform - Uwe Kunert; Hartmut Kuhfeld (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
In this study we first analyze duties on passenger cars in 27 European countries. Taxes and fees related to the registration, ownership and use of cars are assessed differently across Europe, and their rates vary significantly. We find that the annual taxes levied on specific types of cars differ across countries by a factor of up to four, while the various kinds of duties levied account for extremely diverse shares of the entire car-related tax burden and give rise to very different ratios of fixed and variable components in the taxes levied. Given the importance of taxation systems for market and competitive conditions, the European Commission is seeking to achieve reciprocal alignment of the various systems. The Commission has also proposed that greater importance be given to environmental criteria in the assessment of vehicle related taxes. Effectively in some countries, the registration taxes represent a significant burden on the acquisition of new vehicles; this factor reduces market transparency and may mean that taxes are levied twice. Only in a few countries? tax schemes is fuel consumption taken into account, and then only to a marginal degree. It is thus necessary to modify and simplify the tax systems in Europe, because it is crucial that the traffic sector contribute more to climate protection, and because motor vehicles impair local air quality. In this context, the overall structure of the various charges to passenger cars should be rebalanced, with CO2 emissions not being the sole focus.
Keywords: 330